A Fundamental Approach to Electrochemical Analyses on Chemically Modified Thin Films for Barrier CMP Optimization. (9th April 2019) - Yagan, Rawana; Basim, G. Bahar
Abstract : Chemical Mechanical Planarization (CMP) process development for 10nm nodes and beyond demands a systematic understanding of atomic-scale chemical and mechanical surface interactions for the control of material removal, selectivity, and defectivity. Particularly the CMP of barrier/liner films is challenging with new materials introduced to better adhere the contact metal at the interface and limit the probability of metal diffusion to the transistors. The relative selectivity of the CMP removal rates of the barrier materials against the contact metal needs to be controlled depending on the integration scheme. This paper focuses on understanding the barrier CMP process selectivity on the model W/Ti/TiN applications through electrochemical evaluations and chemically modified thin film analyses. Ex-situ electrochemical evaluations are conducted on the W/Ti/TiN system to evaluate the passivation rates in various slurry formulations as a function of the slurry chemistry and the abrasive particle solids loading. Results of the passivation rates are compared to the removal rate selectivity and the post CMP surface quality on blanked W, Ti, and TiN films. A new methodology for CMP slurry formulations through ex-situ electrochemical analyses is outlined for new and more challenging barrier films while simultaneously highlighting an approach for corrosion prevention on the metallic layers.